2018
DOI: 10.24840/2183-6493_003.002_0001
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Milling of Gamma Titanium Aluminides

Abstract: Intermetallic titanium aluminide alloys are used in the high technology engineering field with the goal of achieving weight reduction in different components, exposed to corrosive environments and high temperatures in aeronautical and automotive industries. Despite their attractive properties such as low density, high strength, high stiffness and good corrosion, creep and oxidation resistance, the machinability of titanium aluminide alloys is difficult due to its high hardness, chemical reactivity, and low duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although some research can be found in the literature regarding the experimental and analytical evaluation of traditional machining processes such as turning [15], drilling [16], and milling [17] on titanium aluminides, the number of studies is quite low in comparison to other titanium alloys, so further efforts are needed to find the best cutting conditions. Most of the studies completed on turning conclude the need to perform the process with low cutting speeds, avoiding thermal increase and rapid deterioration of the tool [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although some research can be found in the literature regarding the experimental and analytical evaluation of traditional machining processes such as turning [15], drilling [16], and milling [17] on titanium aluminides, the number of studies is quite low in comparison to other titanium alloys, so further efforts are needed to find the best cutting conditions. Most of the studies completed on turning conclude the need to perform the process with low cutting speeds, avoiding thermal increase and rapid deterioration of the tool [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the difficulty of carrying out the machining processes is seriously limiting the industrial applicability of these materials. Titanium aluminides are classified as difficult-to-cut materials, with a much more complex machinability than other conventional titanium alloys [9]. Due to their mechanical properties, high chemical affinity with most cutting tool materials and high coefficients of friction, extreme temperatures are generated during the cutting, leading to accelerated wear of the inserts and rapid tool failure, together with surface damage of the machined parts [10], [11].…”
Section: Introductionmentioning
confidence: 99%